MEMBACA KONSEP KASIH DALAM INJIL YOHANES MENGGUNAKAN LENSA HERMENEUTIK MISIONAL - Matheus Mangentang; Tony Salurante (Phronesis: Jurnal Teologi dan Misi, 2021)
This research attempt to show values from the concept of love in John's theology, especially in the Gospel, using a missional approach as a hermeneutic. This approach shows that the source of love is in the middle of the world because of God's mission to save humanity. Love is essential that unites the relationship between man and God. In addition, God can be known in the world because demonstrated by Christ in the cross. The church as a community of believers become a source of love because Her lives in the true love and fruitful. Love as one of the main teaching in the Gospel of John becomes a special theme in understanding God's mission from beginning to the end. Mainly in the modern context of religiousity and commitment in relationships between people around the church.